2008
DOI: 10.1038/ajh.2008.156
|View full text |Cite
|
Sign up to set email alerts
|

 -Blockers Reduce Aortic Stiffness in Hypertension but Nebivolol, Not Atenolol, Reduces Wave Reflection

Abstract: The beta-blockers, atenolol and nebivolol, have a similar effect in reducing arterial stiffness in the large elastic aorta, largely secondary to BP reduction. Nebivolol, in contrast to atenolol, has an effect on small muscular arteries, increasing PP amplification and reducing wave reflection, possibly because of increased levels of nitric oxide (NO). Such ancillary properties may impart important distinct hemodynamic effects, and therefore beta-blockers cannot be regarded as a homogeneous group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
4
16

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 15 publications
(21 reference statements)
12
78
4
16
Order By: Relevance
“…In the present study, while atenolol reduced brachial BP effectively as assessed by brachial sphygmomanometry, it does not reduce augmentation pressure or index, a finding that has been observed in other studies. 3,20 In fact, augmentation pressure and augmentation index were increased with atenolol monotherapy in this study (Table II). Recent data from the Conduit Artery Function Evaluation (CAFE) have spotlighted the potential importance of these two parameters in reducing coronary events.…”
Section: Discussionsupporting
confidence: 51%
“…In the present study, while atenolol reduced brachial BP effectively as assessed by brachial sphygmomanometry, it does not reduce augmentation pressure or index, a finding that has been observed in other studies. 3,20 In fact, augmentation pressure and augmentation index were increased with atenolol monotherapy in this study (Table II). Recent data from the Conduit Artery Function Evaluation (CAFE) have spotlighted the potential importance of these two parameters in reducing coronary events.…”
Section: Discussionsupporting
confidence: 51%
“…Although AIx and HR are inversely related, a small decrease in HR (8 beats per min) occurs with a decrease in AIx after vasodilating drug therapy. 31 The observed 5 beats per min decrease following WBV training did not influence the changes in AIx and AIx@75. Thus, it is likely that repetition of the acute vascular effects during 6 weeks would be responsible for the improvements in baPWV and AIx after WBV training.…”
Section: Discussionmentioning
confidence: 79%
“…Two short-term studies (4 to 5 weeks) reported that NEB had a significantly greater effect on central pulse pressure compared with the cardioselective BB atenolol. 8, 13 Dhakam et al 8 in their study demonstrated that overall aortic pulse pressure was 4 mm Hg lower after NEB therapy than after atenolol therapy. 8 Moreover, the results from the Conduit Artery Function Evaluation Study 6 indicate that even a 3-mm Hg reduction in central pulse pressure was associated with better cardiovascular outcome.…”
Section: Bb and Reduction In Central Aortic Pressurementioning
confidence: 96%
“…Previous studies have demonstrated a significant reduction in PWV after treatment with NEB. 8,13 It has been suggested that the effect of BB on PWV may be related to the concomitant effect of reduction in mean arterial pressure, sympathetic tone, and HR. Consequently, one possible explanation for the nonsignificant change in PWV in the present study is also the significantly smaller reduction in HR during the 1-year treatment period (Ϸ6 bpm).…”
Section: Bb and Reduction In Central Aortic Pressurementioning
confidence: 99%